Efektivitas Pelatihan Menjahit dengan Mesin Dalam Meningkatkan Produktivitas Wanita di Masa Pandemi Covid 19: Studi Kasus UPT. Balai Latihan Kerja Deli Serdang - Bimantaka, Yudi; Aisyah, Siti (At-Tadris: Journal of Islamic Education, 2023)
This research is set against the backdrop of the increasing number of unemployed and the declining Indonesian economy during the Covid 19 pandemic, and the number of women who cannot do an activity that produces. So the author conducted a study with the title Effectiveness of Sewing Training With Machines In Increasing Women's Productivity During the Covid 19 Pandemic (UPT Case Study). Deli Serdang Work Training Center), The aim to find out the training at BLK Lubuk Pakam is already effective to increase women's productivity and reduce the number of unemployed. The results showed: 1) the participants took sewing training because they wanted to hone their skills to be proficient in sewing and increase their income. 2) All participants understand what is taught during training even now they also still remember the materials provided during training. 3) Many benefits are provided after participating in Sewing With Machine training at BLK Lubuk Pakam. 4) Sewing With Machine training at BLK Lubuk Pakam the participants have 70% got a job and opened a small business at home, if viewed as a whole, and understand the materials provided to date, benefits in everyday life. If viewed from the whole can be concluded Sewing Training With Machinery in BLK Lubuk Pakam is already effective and needs improvement so that the quality of the workforce is better and can reduce the unemployment rate.